A sustainable information security framework for e-Government – case of Tanzania - Wangwe, Carina Kabajunga; Eloff, Maria Margaretha; Venter, Lucas (Technological and Economic Development of Economy, 2012)
The government of Tanzania adopted an e-Government strategy in 2009 that is aimed at improving efficiency in government and providing better services to citizens. Information security is identified as one of the requirements for the successful e-Government implementation although the government has not adopted any standards or issued guidelines to government agencies with regards to information security. Comprehensive addressing of information security can be an expensive undertaking and without guidelines information security implementations may be more prone to failure. In a resource poor country such as Tanzania, there is a need for a cost effective and sustainable means of addressing information security in e-Government implementations. In this paper the authors present a case study of an e-Government interaction between a ministry and a government agency and the information security challenges identified in the implementation. In order to address these challenges an information security framework is conceptualized using action research. The framework is applied in the case study to address the identified challenges and the means to address future challenges in a sustainable manner is identified. Finally, the proposed framework is evaluated against Tanzanian and international metrics.